La redacción académica desde el enfoque por competencias en la enseñanza del nivel superior - Rodríguez Tuesta, Betty (2023)
The objective of this article is to analyze the concepts of academic writing, competency-based approach, higher education; complex thought from the university vision, in order to understand what are the implications of academic writing at the higher level, what academic literacy consists of and what are the challenges of higher academic writing from the competency-based approach. The methodology used consisted of a narrative review with a search strategy according to the subject, authors, based on the meticulous review of 40 academic articles in English with updated bibliography available in indexed journals. The analysis carried out allows us to conclude that academic writing from the competency-based approach is essential for academic and professional performance inside and outside the university. To achieve these academic writing processes, it is necessary that writing at the university be a priority in all areas of knowledge throughout the student's training process. Therefore, it is urgent to advance in a more interdisciplinary and comprehensive vision of reading and writing, respecting the processes to achieve effective results.